Analisis Butir Soal Pilihan Ganda Menggunakan Anates pada Penilaian Tengah Semester Kelas VII D SMP Negeri 1 Ngajum Kabupaten Malang - muh sholeh mawardi; Anies Fuady; Sunismi Sunismi (Wahana, 2023)
Evaluation or assessment of learning is one part of a series of learning processes. A quality assessment device is able to measure what will be measured. In fact not all teachers do an analytical test first before the manuscript test is used. Analysis of question items is a series of activities carried out in assessing the quality of question items. Validity provides an idea which the assessment tool can measure exactly what is to be measured. The reliability of an assessment tool is to measure the extent to which the measurement results with the assessment tool are stable or consistent. Anates is an application or software developed to help carry out the analysis of question items quickly and practically. A study was carried out with the title "Analysis of Multiple Choice Test Items Using Anates in the Midterm Assessment of Class VII D of SMP Negeri 1 Ngajum, Malang". The use of the Anates application version 4.0.9 has proven effective in making it easier for educators to analyze multiple choice test quickly. Based on the results of the analysis, it was concluded that the correlation of question number 4 compared to the total score is very significant, while the correlation of questions number 6, 7, and 8 is significant. The differentiating power of questions number 1, 4, 6, 7, 8 and 10 is very good, acceptable while question number 9 the differentiating power needs to be improved. Questions number 1, 2, and 5 are very easy, questions number 3 are easy, questions number 7, 8, 10 are medium, questions number 4, 6, and 9 are difficult. Distractors numbered 1B, 1D, 3B, 3D, 4D, 5D, 6D, 7B, 8B should be replaced, while distractors numbers 1C, 6B, 7A, and 7C need to be revised.